Pengaruh Pelatihan terhadap Kinerja Pegawai pada Kantor BPJS Kesehatan Kabupaten Pangkep - fausiah fausiah; hafipah hafipah; Andi irfan (Jurnal Mirai Management, 2022)
This research was conducted directly at the District Health Office of the BPJs. Pangkep in mid-March to mid-May 2022. Sampling in this study used 30 respondents. The technique of collecting data is by using a questionnaire distributed to respondents. The research variables are training (X), and employee performance (Y). This study uses validity and quantitative analysis, to test the level of reliability using Cronbach's Alpha then the data is processed by Simple Linear Regression Analysis. Hypothesis testing using t test with a significance level of 5%. This study uses the SPSS Version 25 tool. From the results of simple linear regression analysis, it shows that employee performance is influenced by the training variable. The result of determination (R2) is one of the dependent variables. That is equal to 0.273 which means that the performance variable is able to explain the employee's performance by 27.3% while the remaining 72.7% is influenced by other variables not examined. From the results of the t-test calculation, it can be seen that the training variable has a partial effect on employee performance. Keywords: Training, Employee Performance